Special papersTranscatheter aortic valve implantation complicated by acute pericardial tamponade - Możeńska, Olga; Suwalski, Piotr; Pawlak, Agnieszka; Kulawik, Tomasz; Byczkowska, Katarzyna; Gil, Robert J. (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2014)
Transcatheter aortic valve replacement (TAVR) is now an accepted standard of care for patients with symptomatic severe aortic stenosis who are not candidates for surgery or have high surgical risk. Despite its more widespread adoption as a treatment option and increasing experience of centers, TAVR is still associated with several complications. We therefore report a case of TAVR complicated by acute pericardial tamponade, one of the most severe potential complications of this procedure. We describe the way we approached the problem and we try to give a potential take-home message for others who might encounter such a situation in their own cath lab.